In situ Vaccine Plus Checkpoint Blockade Induces Memory Humoral Response - Baniel, Claire C.; Heinze, Clinton M.; Hoefges, Anna; Sumiec, Elizabeth G.; Hank, Jaquelyn A.; Carlson, Peter M.; Jin, Won Jong; Patel, Ravi B.; Sriramaneni, Raghava N.; Gillies, Stephen D.; Erbe, Amy K.; Schwarz, Ciara N.; et al. (Frontiers in Immunology, 2020)
In a syngeneic murine melanoma (MEL) model, we recently reported an in situ vaccination response to combined radiation (RT) and intra-tumoral (IT) injection of anti-GD2 hu14.18-IL2 immunocytokine (IC). This combined treatment resulted in 71% complete and durable regression of 5-week tumors, a tumor-specific memory T cell response, and augmented response to systemic anti-CTLA-4 antibody checkpoint blockade. While the ability of radiation to diversify anti-tumor T cell response has been reported, we hypothesize that mice rendered disease-free (DF) by a RT-based ISV might also exhibit a heightened B cell response. C57BL/6 mice were engrafted with 2x106 GD2+ B78 MEL and treated at a target tumor size of ~200mm3 with 12 Gy RT, IT-IC on day (D)6-D10, and anti-CTLA-4 on D3, 6, and 9. Serum was collected via facial vein before tumor injection, before treatment, during treatment, after becoming DF, and following rejection of subcutaneous 2x106 B78 MEL re-challenge on D90. Flow cytometry demonstrated the presence of tumor-specific IgG in sera from mice rendered DF and rejecting re-challenge with B78 MEL at D90 after starting treatment. Consistent with an adaptive endogenous anti-tumor humoral memory response, these anti-tumor antibodies bound to B78 cells and parental B16 cells (GD2-), but not to the unrelated syngeneic Panc02 or Panc02 GD2+ cell lines. We evaluated the kinetics of this response and observed that tumor-specific IgG was consistently detected by D22 after initiation of treatment, corresponding to a time of rapid tumor regression. The amount of tumor-specific antibody binding to tumor cells (as measured by flow MFI) did not correlate with or host animal prognosis. Incubation of B16 MEL cells in DF serum, vs. naïve serum, prior to IV injection, did not delay engraftment of B16 metastases and showed similar overall survival rates. B cell depletion using anti-CD20 or anti-CD19 and anti-B220 did not impact the efficacy of ISV treatment. Thus, treatment with RT + IC + anti-CTLA-4 results in adaptive anti-tumor humoral memory response. This endogenous tumor-specific antibody response does not appear to have therapeutic efficacy but may serve as a biomarker for an anti-tumor T cell response.